Ciprofloxacin for the treatment of Cardiobacterium hominis prosthetic valve endocarditis. (2018) - Avery, Lisa M.; Felberbaum, Catherine B.; Hasan, Muhammad
Abstract: Prosthetic valve endocarditis due to Cardiobacterium hominis is rare and recommended therapy includes a third generation cephalosporin. We report a case of Cardiobacterium hominis endocarditis post transcatheter aortic valve replacement in a patient with significant beta-lactam antimicrobial sensitivities who was successfully treated with ciprofloxacin monotherapy in conjunction with surgery.